Antileishmanial activity evaluation of poly(thymolformaldehyde)—A biobased material from thymol - Parolin, Giovana A.; Passero, Luiz Felipe D. [UNESP]; Lago, João Henrique G.; Péres, Laura Oliveira (Elsevier, 2021)
A new biobased compound was prepared from commercially available monoterpene thymol, obtained from the essential oil of a cultivated plant, Thymus vulgaris L. (Lamiaceae), together with formaldehyde. The final product, poly(thymolformaldehyde), namely PTF, was characterized by infrared spectroscopy (FTIR), nuclear magnetic resonance (NMR), UV–vis spectroscopy, fluorescence, gel permeation chromatography (GPC), thermogravimetric analysis (TGA), and differential scattering calorimetry (DSC). NMR associated with FTIR data analysis evidenced the occurrence of polymerization at C-1 and C-5 positions of thymol. UV–vis and fluorescence analysis showed that the prepared material exhibited absorption and emission bands at 285 and 313 nm, respectively. GPC data analysis displayed a polydisperse material (PDI = 1.99) with a molar mass of approximately 1375 Da, while TGA analysis showed a high thermal resistance (ranging from 150 to 800 °C). PTF was evaluated against promastigote forms of Leishmania (Leishmania) amazonensis and exhibited effective concentration 50 % (EC50) of 8.4 ± 0.8 μg/mL as well as reduced toxicity to macrophages (cytotoxic concentration 50 % - CC50 > 100 μg/mL and SI > 11.9). Therefore, the effects of PTF against L. (L.) amazonensis, together with its simple preparation using commercially available reagents (thymol and formaldehyde), suggest that this polymer could be a promising candidate for new biobased drugs to treat cutaneous leishmaniasis.
Keywords: Biobased material; Leishmania (L.) amazonensis; Polymerization; Thymol